The Influence of Transformational Leadership, Career Development and Work Ethic on Job Satisfaction with an Impact on Employee Performance at the Tangerang DPRD Secretariat - Hamsinah Hamsinah (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2020)
This study aims to determine the effect of transformational leadership, career development, and work ethic on job satisfaction, impacting employee performance at the Tangerang DPRD Secretariat. The method used is explanatory research with a sample of 125 respondents. The analysis technique uses statistical analysis with regression testing, coefficient of determination, and hypothesis testing. The results of this study Transformational Leadership has a significant effect on job satisfaction by 26.8%; hypothesis testing obtained a significance of 0.000 <0.05. Career development significantly affects job satisfaction by 40.2%; hypothesis testing obtained a significance of 0.000 <0.05. Work ethic significantly affects job satisfaction by 28.1%; hypothesis testing obtained a significance of 0.000 <0.05.